An examination of the works of Flourish for wind band by Ralph Vaughn Williams, Air for band by Frank Erickson, An American elegy by Frank Ticheli, Rough riders by Karl King, arranged by James Swearingen - Johnson, Travis (Kansas State University, 2010)
This document was written after examination, research, score analysis, and lesson planning in preparation for the Graduate Conducting Recital of Travis M. Johnson. This recital was held on Monday, March 8, 2010 at the Cheney High School Auditorium at 6:00 pm. A philosophy of Music Education and criteria for quality literature selection is followed by the theoretical and historical analysis of four works; Flourish for Wind Band by Ralph Vaughn Williams, Air for Band by Frank Erickson, An American Elegy by Frank Ticheli, and Rough Riders by Karl King arranged by James Swearingen. Lesson plans, rehearsal aids, warm up exercises, and student assignments are included in the examination of this process.
Keywords: Frank Ticheli; An American elegy; Frank Erickson; Air for band; Karl King; Rough riders; Ralph Vaughn Williams; Education, Music (0522)